Tingginya Angka Cerai Gugat di Kabupaten Sumenep & Dampaknya bagi Anak - Sofia Mubarokah Sa'bana; Rusdiana Navlia (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2023)
The background of this research is the divorce factor, where the problems are not always caused by the wife, such as the husband's infidelity, household neglect and domestic violence, economic factors and and other factors. Conflict is a natural thing when both parties are willing to give in and can understand by taking the positive side, but if the conflict is allowed to continue it will have a negative impact which will ultimately lead to divorce. Divorce itself has a huge impact on children's development. This field research used a case study approach carried out at the Sumenep Religious Court. The results of this research are that the most dominant factor in filing for divorce at the Sumenep Religious Court is due to ongoing disputes caused by economics, abandonment of one party (neglect), and domestic violence.